Comprehensive Energy Management - Safe Adaptation, Predictive Control and Thermal Management - Watzenig, Daniel; Brandstätter, Bernhard (Automotive Engineering : Simulation and Validation Methods, Automotive Engineering : Simulation and Validation Methods,, 2018)
The book discusses the emerging topic of comprehensive energy management in electric vehicles from the viewpoint of academia and from the industrial perspective. It provides a seamless coverage of all relevant systems and control algorithms for comprehensive energy management, their integration on a multi-core system and their reliability assurance (validation and test). Relevant European projects contributing to the evolvement of comprehensive energy management in fully electric vehicles are also included. This volume includes contributions on model based functional safety and fault-tolerant E/E architectures, advanced control making use of external information (from a cloud) as well and thermal management as a central part for energy optimization and finally some aspects on fuel cells. The second volume (ISBN .....) includes chapters on ECO driving and ECO routing covering different approaches for optimal speed profiles for a given route (mostly interconnecting withcloud data). .